2020
DOI: 10.1021/acs.jafc.0c03005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption and Tissue Distribution of Aza-Sugars from Mulberry Leaves and Evaluation of Their Transport by Sugar Transporters

Abstract: Mulberry leaves are rich in aza-sugars, particularly 1-deoxynojirimycin (DNJ), fagomine, and 2-O-α-d-galactopyranosyl-1-deoxynojirimycin (GAL-DNJ), which have antidiabetes and antiobesity properties. To help us understand the mechanisms of action of aza-sugars, pharmacokinetic studies are necessary. Therefore, in this study, we evaluated and compared the absorption and organ distribution of these aza-sugars in rats. Following oral intake, DNJ exhibited the highest plasma concentration followed by fagomine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…These results suggested that in the M. australis fruit extract, 1-DNJ is not a main inhibitor of α-amylase, but is a main inhibitor of α-glucosidase, and that neither fagomine nor GAL-DNJ is a main inhibitor of α-amylase or α-glucosidase. Amézqueta et al (2017) reported that orally administered fagomine in rats was partly absorbed but mostly excreted in feces within 24 h. Takasu et al (2020) reported that orally administered GAL-DNJ in rats is partly degraded into galactose and 1-DNJ. Considering these results, the contribution of fagomine and GAL-DNJ to the inhibition of α-glucosidase cannot be underestimated from our results.…”
Section: Morus Australis Fruitsmentioning
confidence: 99%
“…These results suggested that in the M. australis fruit extract, 1-DNJ is not a main inhibitor of α-amylase, but is a main inhibitor of α-glucosidase, and that neither fagomine nor GAL-DNJ is a main inhibitor of α-amylase or α-glucosidase. Amézqueta et al (2017) reported that orally administered fagomine in rats was partly absorbed but mostly excreted in feces within 24 h. Takasu et al (2020) reported that orally administered GAL-DNJ in rats is partly degraded into galactose and 1-DNJ. Considering these results, the contribution of fagomine and GAL-DNJ to the inhibition of α-glucosidase cannot be underestimated from our results.…”
Section: Morus Australis Fruitsmentioning
confidence: 99%
“…Another report claimed morphine brain accumulation of ~ 0.01% from oral dose of 9 mg/kg 41 . Considering a brain-transportable natural compound, 1-deoxynojirimycin showed an appropriate accumulation of ~ 1.2 pmol/mg in the brain of Sprague–Dawley rats after oral administration at 40 μmol or 6.5 mg/kg 42 , 43 . Conversely, despite the low accumulation or poor uptake ratio of 0.0037% of Tyr-[ 13 C 5 , 15 N]Pro in the mouse brain at 10 mg/kg observed in the present oral administration study, we have previously shown significant improvement in impaired memory in amyloid β-induced AD mice following daily Tyr-Pro intake (100 mg/kg, twice a day) for 16 days 18 suggesting that low Tyr-Pro accumulation, even at 100 mg/kg, would be effective when one expects a preventive effect against the onset of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy had a significant effect on triglycerides, which reduced from 310 80 mg/dL at standard to 242 76 mg/dL at 12 weeks, but no other lipids changed statistically significantly (29). Mulberry leaves can also be made into tea.…”
Section: Beneficial Effect In Hyperlipidemiamentioning
confidence: 99%